The Administrative Model of Wongdeaun Akomsurathan Vocational Training Center of Thai People under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province - Phograjang, Uthaiwan (Journal of Research and Development Institute Rajabhat Maha Sarakham University, 2020)
The main purpose of this research aimed to develop the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province. 1) To study the problem condition and the need of administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province. 2) To create the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province. 3) To try out and improve the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province. 4) To evaluate the feasibility, the propriety, and the utility of the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province. The research method was conducted into 4 steps as follows: Step 1: The studying of the problem condition and the need of the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province. Step 2 : The development of the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province. Step 3: The trying out and improving the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province. Step 4: The evaluation of the feasibility, the propriety, and the utility of the management model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province from public hearing. The research findings were as follows: 1. The problem condition and the need shown that the problem condition from document synthesis and related documents, the problem concerned about the management by using of general managements as follows: personnel management, budget management, material and equipment management and management. The part of the need for the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province found that the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province was needed to develop. 2. The administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province comprised 9 administrative aspects were Man, Money, Material, Management, MOU, Minute, Marketing, Mind Service, and Morality. 3. The trying-out results found that the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province was improved the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province province according to the experts’ comments and related to the administration of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province all aspects. 4. The evaluating results of the feasibility, the propriety, and the utility of the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province shown that the administrative model of Wongdeaun Akomsurathan Vocational Training Center training of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province, evaluators agreed correspondingly that the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province was at the highest level ( = 4.997), the utility of the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province was ( = 4.999), the propriety of the administrative model of Wongdeaun Akomsurathan Vocational Training Center of Thai people under the Royal Initiative of Her Royal Highness Princess Maha Chakri Sirindhorn in Uthai Thani province was ( = 4.997), and the feasibility of Thai people under the Royal Initiative of His Majesty the King in Uthai Thani was ( = 4.996)